Role of Na+ co-doping in luminescence enhancement of Bi2O3: Sm3+ nanophosphors. (1st November 2022) - Pandey, Prashant Kumar; Chauhan, Vaibhav; Dixit, Prashant; Pandey, Praveen C.
Abstract: In this paper, we present a comprehensive structural and optical study of alkali metal ion (Na + ) co-doping in samarium-doped bismuth oxide nanophosphors and its role in enhancing the red emission of the phosphors. X-ray diffraction (XRD) analysis ascertains the monoclinic crystal structure (space group P 2 1 /c ) of the synthesized phosphors with crystallite size in the 49–65 nm range. The XRD analysis also reveals an improvement in crystallinity after Na + co-doping in Sm 3+ doped Bi2 O3 phosphors. The HR-SEM micrographs reveal the nanosheet-like morphology and the EDX spectroscopy confirms the presence of all elements in the prepared phosphors. The TEM analysis validates the structural and morphological findings. The UV–Vis–NIR spectroscopic analysis has been carried out to estimate the bandgap as well as to investigate the Urbach energy of the phosphors. An augmentation in bandgap energy (2.784–2.807 eV) is observed for lower Na + co-doping in samarium doped phosphor and shows a decreasing trend with increasing Na + concentration. FTIR spectroscopy was probed to analyze the chemical bonding, modes of vibration, and detection of functional groups in the samples. The room temperature photoluminescence (PL) emission studies were performed under 481 nm excitation which exhibits an explicit redshift of the CIE coordinates. Nearly ten-fold enhancement in the emission intensity was observed in the optimized Bi2 O3 :(5%)Sm 3+ with co-doping of 1% Na + ions. The lifetime of the 4 G5/2 level of the Sm 3+ ions has also increased on doping 1% Na + ions. The thermal stability of the phosphors has been investigated using temperature-dependent PL analysis over the temperature range of 303–453 K. The correlated color temperature (CCT) analysis of the samples reveals that the prepared nanophosphors are promising and potential red-emitting phosphors to realize efficient optoelectronic and display devices. Highlights: The Na + co-doping supports the crystal growth and helps in improving the PL emission intensity. HR-SEM and TEM analyses confirm the nanosheet-like morphology of the phosphors. The PL emission intensity was increased nearly ten-times after 1% Na + co-doping in Bi2 O3 : (5%)Sm 3+ phosphor. The role of Na + in the emission enhancement and their correlations with structural analysis has been discussed. The thermal stability of the phosphors was studied via temperature-dependent PL analysis.